Outcome of Venous Supercharged Pedicled Anterolateral Thigh Flap for Reconstruction of Soft Tissue Defect around the Knee Joint - Arju, Khondokar Shohana; Dash, Pradip Chandra; Ahmed, Tanveer; Reza, Humayun Kabir; Biswas, Gobinda; Khan, Md Noazesh (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Soft tissue defects around the knee are common following motor vehicle accidents, burns especially electric burn, excision of malignancy etc. Reconstruction of soft tissue defect around the knee needs thin, pliable and tough skin. Recently distally based pedicled anterolateral thigh flap has been used for soft tissue reconstruction for its several advantages like long pedicle, sufficient amount of soft tissue and less donor site morbidity. But it has tendency towards venous congestion and this can be overcome with venous supercharging. This study was designed to evaluate the effectiveness of venous supercharging in reducing venous congestion in pedicled anterolateral thigh flap for reconstruction of soft tissue defect around the knee joint. Methods: This prospective observational study was carried out at Department of Plastic Surgery and Burn Unit, Dhaka Medical College Hospital and Sheikh Hasina National Institute of Burn and Plastic Surgery (SHNIBPS), Dhaka from August 2017 to June 2019. Twenty (20) patients who presented with defect around the knee were included in this study according to inclusion and exclusion criteria. Results: Maximum patients 5(25%)were day labour and wounds were created by MVA in most of the cases10(50%).Most common site was anterior aspect of knee joint 8(40%).The dimension of the wound size ranged from 5×3cm upto 7×14cm. Majority of the wounds ranged from 15×13cm to 17×14cm. The flap size ranged from 6×3.5cm upto 20×18cm. 18 (90%) flaps had no venous congestion, but 2(10%) cases had it. All flaps (20) survived well, 18 cases had acceptable scar and in 2 cases infection occurred. Regarding functional outcome of knee joints, 15 (75%) patients had full range of motion and 5(25%) patients had 5p -10p restriction in flexion of knee joints. Final outcome was found excellent in 16(80%) and satisfactory in 4(20%) cases. Conclusion: Venous supercharging in pedicled anterolateral thigh flap for soft tissue defect around the knee joint have shown to be effective in reducing venous congestion. J Bangladesh Coll Phys Surg 2022; 40: 233-239